Análise da cinética da transformação isotérmica a 665ºC e caracterização dos seus efeitos na microestrutura e na dureza do aço SAE 1080. - Oliveira, Gabriel Almeida de (2019)
The current study seeks to evaluate the kinects of the isothermal transformation at 665 °C of a SAE 1080 carbon steel through inspection of its microstructural gradual shifts and to examine how the hardness changes during transformation. Initially, emission spectrometry provided the chemical composition of the steel specimen in order to investigate its particularities. Then, six samples cut out from the specimen were heat treated in three continuous stages: austenitization at 850 °C for 15 minutes; isothermal treatment at 665 °C for 90 to 300 seconds with individual value per sample; water quenching at room temperature. Metallographic and volume fraction estimation enables identifying and correlating the observed microstructure with ongoing isothermal transformation, furthermore, Vickers hardness tests showed its influence on the mechanical properties of the material. Chemical analysis revealed that the specimen present a silicon content close to the maximum limit (0.60wt%) allowed by the norm NBR NM 87. The micrographs exhibited a microstructure constituted of martensite, proeutectoid cementite, perlite and nonmetallic inclusion whose morphology indicates that they are duplex inclusions composed of silicates and sulphides, both of manganese. The volume fraction estimations demonstrated the progress of the isothermal transformation, thus, at 90 seconds of treatment the microstructure is constituted of 98.25% martensite, while at 300 seconds it’s composed of 97.82% perlite. The obtained hardness data described a gradual softening of the material during the transformation; starting with average hardness of 794 HV that decreases to 282 HV, a typical behavior of the transition from martensite to perlite. Additionally, these results indicates that the interlamellar spacing of the obtained perlite is 0.31 μm. Applying the kinects analysis described by (Christian, 2002) to the volume fraction results leads to the determination of an Avrami equation that describes the observed isothermal transformation, further, the equation indicates that the transformation occurs via heterogeneous nucleation with tridimensional nuclei growth.